Die deutsche Briefmarke als Kulturträger: Zum Einsatz von Briefmarken in der Lehre des Deutschen als Fremdsprache - Wagner Doris (Germany, 2022)
This contribution seeks to foster the use of German stamps as a part of the DaF (Deutsch als Fremdsprache, German as a foreign language) education at the universities. Stamps are carriers of culture and, thus, represent a nation both inside and outside its geographical borders. Due to this double function stamps are a valuable material to be used in lessons focusing on culture and country knowledge. Stamps can be used to introduce, counterpoint, or to deepen a certain topic or theme. Further, stamps are a good material for contrastive scrutiny, an aspect enjoying a central position in the DaF education. This contribution presents a short history of the German stamps from the beginning till today and discusses questions related to the responsibilities for issuing stamps in Germany. A short excursion will evidence how stamps could be abused for propaganda purposes. The excursion, together with several other examples presenting the thematic variety of stamps, should – even if not explicitly stated – encourage individual use of stamps as a part of the education. After a short description of the structure of the country knowledge and culture courses at the University of Turku, the German stamp “175 years of Deutschlandlied” is used as a concrete case study in order to exemplify how this stamp can be used to handle the topic “German national anthem” as a part of a master’s level course.
Brückenschläge Nord: Landeskunde an der Schnittstelle von Schule und Universität